Prior knowledge in recalling arguments in bioethical dilemmas - Schmidt, Hiemke K.; Rothgangel, Martin; Grube, Dietmar (Frontiers in Psychology, 2015)
Prior knowledge is known to facilitate learning new information. Normally in studies confirming this outcome the relationship between prior knowledge and the topic to be learned is obvious: the information to be acquired is part of the domain or topic to which the prior knowledge belongs. This raises the question as to whether prior knowledge of various domains facilitates recalling information. In this study 79 eleventh-grade students completed a questionnaire on their prior knowledge of seven different domains related to the bioethical dilemma of prenatal diagnostics. The students read a text containing arguments for and arguments against prenatal diagnostics. After one week and again 12 weeks later they were asked to write down all the arguments they remembered. Prior knowledge helped them recall the arguments one week (r = .350) and 12 weeks (r = .316) later. Prior knowledge of three of the seven domains significantly helped them recall the arguments one week later (correlations between r = .194 to r = .394). Partial correlations with interest as a control item revealed that interest did not explain the relationship between prior knowledge and recall. Prior knowledge of different domains jointly supports the recall of arguments related to bioethical topics.